2006
DOI: 10.4269/ajtmh.2006.74.1034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Education on Knowledge, Agricultural Practices, and Community Actions for Mosquito Control and Mosquito-Borne Disease Prevention in Rice Ecosystems in Sri Lanka

Abstract: Mosquito-borne diseases are a major public health threat in Sri Lanka. A 20-week pilot education program to improve community knowledge and mosquito control with participatory and non-chemical approaches was developed, implemented, and evaluated using pre-educational and post-educational surveys in two intervention and two comparison villages. Correlates of baseline knowledge were sex, number of family members, ratio of family members with malaria history, school education level, and availability of electricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 17 publications
(19 reference statements)
2
55
0
Order By: Relevance
“…23 The study also reported a 60% increase in the use of bednets, also attributable to the intervention, indicating there was an increased awareness about personal protection. The same researchers suggested that the role of farmers in vector management was most important during the short rainy season, when ecosystem management is associated with reduced densities of anopheline mosquitoes, thus providing an opportunity to interrupt local transmission of malaria.…”
Section: Addressing the Problemsmentioning
confidence: 84%
“…23 The study also reported a 60% increase in the use of bednets, also attributable to the intervention, indicating there was an increased awareness about personal protection. The same researchers suggested that the role of farmers in vector management was most important during the short rainy season, when ecosystem management is associated with reduced densities of anopheline mosquitoes, thus providing an opportunity to interrupt local transmission of malaria.…”
Section: Addressing the Problemsmentioning
confidence: 84%
“…collection of small containers), none of which have a proven efficacy to prevent malaria in Africa. Teaching evidence-based methods needs to take the local ecology of mosquitoes into account [52,84-86] because methods which are appropriate in one area might not be in another. While vegetation clearance can help control shade loving malaria vectors it will increase the abundance of An.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few projects show community-led vector control that goes beyond personal protection measures e.g. environmental modifications and larviciding [48-52]. …”
Section: Introductionmentioning
confidence: 99%
“…Yasuoka and Levins 2007b;Yasuoka et al 2006a;Yasuoka et al 2006b). As clearly presented by Prothero (1965), the commodification of agriculture in Africa led to a pattern of seasonal movement among landless farmers, migrating in order to work in commercially oriented estates, and this, subsequently, allowed for the invasion of parasites in new ecosystems where most of the native population were not immune to malaria infections.…”
Section: Ecological Interactionsmentioning
confidence: 99%
“…As we discussed earlier, a major underlying force in the spread of malaria, and even in the genetic structure of human populations, has been agriculture-a unique feature of the human species, deeply entangled with malaria historical dynamics in societies. For malaria, examples supporting its socialized nature are abundant: children of the poorest households are more likely to suffer malaria ; malaria transmission risk is reduced by a factor of 25 in countries with good health services (e.g., those able to provide prompt treatment) (Bouma 2003); educated communities are better at managing malaria risk factors, especially by reducing mosquito sources without compromising agricultural productivity (Yasuoka et al 2006b); and only when robust structures of socioeconomic development have been present has malaria control been effective in the long run (Celli 1977;Kitron 1987;Lindsay and Birley 2004). Thus, only the integration of knowledge from the various fields discussed in this paper will provide new insights into the biology of malaria.…”
Section: Schmalhausen's Law and Diseases Inmentioning
confidence: 99%